The most-liked and least-liked television personalities and programs perceived by selected students of the San Miguel High School, Bulacan as related to some variables - Wichian Dechgoontong 1948- (1975)
This study aimed to look into the perceptions of selected high school students regarding their most-liked and least-liked television personalities and program references. It also determined the characteristics of the most-liked and least-liked television personalities as perceived by the respondents.
Thesis (M.Ed.)--University of the Philippines
Keywords: Television broadcasting -- Philippines; Television audiences